Mula tarima hanggang at iba pang mga tula at awit - Acosta, Ericson (University of the Philippines Press, 2015)
"With his book Mula Tarima Hanggang, At Iba Pang mga Tula at Awit, Ericson Acosta, according to Jose Maria Sison, "joins the ranks of Filipino poets who live up to a great tradition of poetry and continue to carry on the noble mission of serving the people in their struggle for freedom from foreign and feudal domination. Acosta transforms his suffering in prison and his struggle for freedom as a metaphor for the intolerable conditions of the Filipino people who are captive in a semicolonial and semifeudal system and for their irrepressible struggle for national independence and democracy.""--Provided by publisher.